2022
DOI: 10.3389/fendo.2022.996228
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization combined with metformin improves the prognosis of hepatocellular carcinoma patients with type 2 diabetes

Abstract: Objective: The study aims to investigate the effect of metformin on Hepatocellular carcinoma (HCC) patients with type 2 diabetes mellitus (T2DM) who received transarterial chemoembolization (TACE) for the first time. Methods:From January 2016 to December 2019, T2DM patients diagnosed with HCC in Shandong Cancer Hospital and treated with TACE were included in this retrospective study. Overall survival (OS) and Progression-free survival (PFS) were compared between patients treated with metformin and other antidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Following title and abstract screening, there were 154 studies deemed eligible for full-text assessment. Eleven studies were ultimately included in the systematic review [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. One study included both pre-clinical and clinical data and was thus considered two separate studies [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following title and abstract screening, there were 154 studies deemed eligible for full-text assessment. Eleven studies were ultimately included in the systematic review [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. One study included both pre-clinical and clinical data and was thus considered two separate studies [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both pre-clinical and clinical studies were identified through the literature search process. Of the 11 total studies included in this systematic review, 5 studies were classified as human preclinical studies [ 87 , 88 , 89 , 90 , 91 ] and 6 studies were classified as human clinical studies [ 82 , 83 , 84 , 85 , 86 , 89 ]. All included studies were full-text publications and were published between 2012 and 2022.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indirectly, metformin suppresses HIF-1α translation, and also reduces intracellular oxygen demand, leading to decreased HIF-1α protein levels and decreased stabilization of HIFs under hypoxic conditions [81,82]. Combining metformin with cTACE has shown promise in clinical studies, with improved overall survival and time to progression in metformin users compared to non-users [83,84]. While metformin is a promising adjunct therapy for HCC patients undergoing cTACE, randomized controlled trials are required to elucidate the optimal dosage and timing of metformin in combination with cTACE.…”
Section: Other Strategies Targeting Tumor Hypoxiamentioning
confidence: 99%